GERAKAN DAN STRATEGI DAKWAH PADA ORGANISASI AHMADIYAH - Ramadhan, Mustarim; Hasanah, Neneng (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2025)
Ahmadiyah is a heretical sect, however, seeing the rapid development of Ahmadiyah teachings which have spread almost throughout Indonesia, it certainly cannot escape the movement and strategy of da'wah carried out by Ahmadiyah. Therefore, this article aims to find out how the da'wah movements and strategies in the Ahmadiyah organization are. This article is qualitative research using the literature study method. The result of the article is that Ahmadiyah uses several media in its da'wah strategy, namely; (1) Da'wah through written media, (2) Da'wah through organizing, and (3) Da'wah through education. And Ahmadiyah has become an exclusive religious sect due to bullying carried out by society against Ahmadiyah followers in several areas.